Electrochemical corrosion behavior of HVOF sprayed WC–12Co coating on H13 hot work mould steel. Issue 6 (20th August 2019) - Weicheng, Kong; Hui, Shen; Jiaxu, Gao; Jie, Wu; Yuling, Lu
Abstract : Purpose: This study aims to investigate the electrochemical corrosion performance of high velocity oxygen fuel (HVOF) sprayed WC–12Co coating in 3.5 Wt.% NaCl solution, which provided a guiding significance on the corrosion resistance of H13 hot work mould steel. Design/methodology/approach: A WC–12Co coating was fabricated on H13 hot work mould steel using a HVOF, and the electrochemical corrosion behaviors of WC–12Co coating and substrate in 3.5 Wt.% NaCl solution was measured using open circuit potential (OCP), potentiodynamic polarization curve (PPC) and electrochemical impedance spectroscopy (EIS) tests. Findings: The OCP and PPC of WC–12Co coating positively shift than those of substrate, its corrosion tendency and corrosion rate decrease to enhance its corrosion resistance. The curvature radius of capacitance curve on the WC–12Co coating is larger than that on the substrate, and the impedance and polarization resistance of WC–12Co coating increase faster than those of substrate, which reduces the corrosion process. Originality/value: The electrochemical corrosion behaviors of WC–12Co coating and substrate in 3.5 Wt.% NaCl solution is first measured using OCP, PPC and EIS tests, which improve the electrochemical corrosion resistance of H13 hot work mould steel.